PEMBUATAN TUTORIAL MEKANISME DINAMIKA DAN ANALISIS KINEMATIK MENGGUNAKAN SOFTWARE CREO PARAMETRIC 2.0 - , ARIF SETIYAWAN ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The development of new products increasingly complex need a good software design. Thus the scientists created software like Creo Parametric 2. In this software contained mechanism features that can make a movement mechanism of components and assist in the design of the product so to provide an analysis of the products made. With so facilitate engineers to create a product that complicated. Beginning of drawing some of the components in the assembly then use the appropriate connection to create the desired movement. To give movement the servo motors can be added into the assembly and the speed of the servo motors can set too. Of the it can be made visualization movement of mechanisms even be made analysis. To give a view of its mechanism in action can be created movie. So that the complex products can be made and identification analysis of the product with so the product design can minimize failure.